Psoriasis in Israel: demographic, epidemiology, and healthcare services utilization. (6th July 2018) - Shalom, Guy; Zisman, Devy; Babaev, Meir; Horev, Amir; Tiosano, Shmuel; Schonmann, Yochai; Comaneshter, Doron; Cohen, Arnon D.
Abstract: Background: Updated data regarding the epidemiology of psoriasis and related healthcare utilization are lacking. Objective: To investigate the epidemiology, comorbidities, healthcare services utilization, and drug use in a large group of patients with psoriasis from Clalit Health Services (CHS) database. Methods: A controlled cross‐sectional study was performed. Case patients were defined when there was at least one documented diagnosis of psoriasis registered by a CHS dermatologist between the years 1998–2016. The extracted data included metabolic, cardiovascular and psychiatric comorbidities; community clinic visits; in‐ and outpatient services utilization profiles and drug use data, which included pharmacy claims of topical and systemic treatments, including phototherapy and climatotherapy. Comparative analysis was performed by a univariate and multivariate analysis, adjusting for age, gender, obesity, and smoking. Results: The study included 118, 680 patients with psoriasis (prevalence of 2.69%) and 118, 680 age‐ and gender‐matched controls. Patients with psoriasis had increased prevalence of metabolic, cardiovascular, and psychiatric illnesses. Psoriasis was significantly associated with an increased healthcare utilization. The mean (SD) number of annual dermatologist clinic visits and emergency room visits was 7.2 ± 12.4 and 2.9 ± 7.7 in psoriasis patients as compared to 2.9 ± 7.9 and 2.7 ± 7.4 in the control group ( P < 0.001). Topical steroids were the most applied treatment in psoriasis patients (15.5%), and topical vitamin D analogs were second in use (14.6%). Traditional systemic treatment for psoriasis was used in 3.8% of the patients, and biologic treatments were used in 1.6% of the patients. Conclusions: Our study quantifies healthcare services utilization and drug use in patients with psoriasis.